Study of Financial Services Authority Policies in Dealing with Corona Virus Disease (Countercyclical) - Heny Yuningrum; Saibatul Aslamiyah (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose -The purpose of this study is to examine the policies determined by the Indonesian Financial Services Authority (OJK) in handling the Corona Virus Pandemic in 2020-2022. Where the policy was made to overcome financing problems so that there would be no bad credit in the following year. Method-The research methods used in this study are qualitative methods by outlining 9 OJK policies in the form of countercyclical.. Result-The results of the study show that there are changes in the policies that have been set by the OJK, including: Extension of the Payment Period for Financing, Affiliate Transactions and Conflict of Interest Transactions extended from a maximum of 6 (six) months to a maximum of 8 (eight) months, there is an increase in Public Company Capital by Granting Preemptive Rights, Public Companies experiencing certain financial conditions as a result of the COVID-19 pandemic can increase capital without granting HMETD in order to improve their financial position and aand the addition of other financial servicesprovider of information technology-based money lending services. Implication - This study provides information to the public and policy observers made by OJK. This information can be a future analysis for policy makers if the pandemic problem occurs again. Originality-This research has the authenticity written by the researcher by analyzing the policies issued by the OJK in overcoming the problem of bad financing due to the Covid Pandemic. The criteria chosen by the researcher also chose the OJK Regulation which specifically discusses the problem of problematic financing during the Covid pandemic.Keywords: PJOK Regulation No. 11/POJK.03/2020, Problematic financing, covid 19